2016
DOI: 10.1002/2016gc006289
|View full text |Cite
|
Sign up to set email alerts
|

Exhumation of the Panama basement complex and basins: Implications for the closure of the Central American seaway

Abstract: The emergence of the Central American isthmus occurred episodically from Eocene to Pliocene time and was caused by a series of tectonic and volcanic processes. Results from zircon U‐Pb geochronology, zircon (U‐Th)/He (ZHe) and apatite (U‐Th)/He (AHe) thermochronology, and zircon Lu‐Hf isotopic data from sedimentary (sandstones and recent river sands) and plutonic rocks from the Azuero Peninsula and Central Panama document the exhumation and uplift history of the Panamanian basement complex. Our data support pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 64 publications
(129 reference statements)
2
18
0
1
Order By: Relevance
“…However, there is an ongoing debate on the timing of the closure of the Isthmus of Panama. Thermochronological data reveal four major cooling events in western and central Panama at 47-42 Ma, 32-28 Ma, 17-9 Ma and 9-0 Ma, which are consistent with the presence of emergent land areas and a reduction of the circulation between the Pacific Ocean and the Caribbean Sea (Ramírez et al, 2016). But the exchange of surface water between the oceans probably stopped much later at 2.…”
Section: The Basement Of the Panamanian Arc Segmentssupporting
confidence: 56%
“…However, there is an ongoing debate on the timing of the closure of the Isthmus of Panama. Thermochronological data reveal four major cooling events in western and central Panama at 47-42 Ma, 32-28 Ma, 17-9 Ma and 9-0 Ma, which are consistent with the presence of emergent land areas and a reduction of the circulation between the Pacific Ocean and the Caribbean Sea (Ramírez et al, 2016). But the exchange of surface water between the oceans probably stopped much later at 2.…”
Section: The Basement Of the Panamanian Arc Segmentssupporting
confidence: 56%
“…This has been interpreted as a direct consequence of the tectonic plate readjustments that followed the collision of the leading edge of the CLIP with northwestern South America (Buchs et al, ; Wegner et al, ). By middle Eocene times, this island arc was being constructed at a well‐established subduction zone in which pyroclastic activity and subaerial exposure have been already documented in the Panama area (Montes, Cardona, et al, ; Ramírez et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Although this sample passed the chi‐square test ( P ( χ 2 ) = 24%), we interpret these ages as a detrital cooling signal, since no field evidence indicating that this unit reached temperatures above ~70°C were observed and because similar AFT cooling ages have been reported for the potential source domains suggested from the sedimentary provenance analysis, as the Penderisco Fm. (AFT ages around 13–14 Ma), the Panama Arc (AFT ages around 40 Ma) (Montes, Cardona, et al, ; Ramírez et al, ). The above corroborates that the middle to late Miocene sediments of the Atrato Basin, which overly the Panama Arc, were sourced by both the South American‐related and the allochthonous Panamanian terranes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Marincovich (2000) suggested that there were multiple mixing events, with one following the first opening of the Bering Strait (4.8-5.5 Ma), and a second mixing event due to the change of direction of flow through the strait, arguably due to shoaling of the Central American Seaway (∼3.6 Ma; Although see Ramírez et al, 2016). These two periods also coincide with eustatic episodes (Marincovich, 2000).…”
Section: Dating Constraints and Uncertaintiesmentioning
confidence: 94%